Analisis Perbandingan Kinerja Keuangan Antara Pendekatan Laporan Laba Rugi Dengan Shari’ate Value Added Statement (SVAS) pada Koperasi Syariah Benteng Mikro Indonesia - Samino Hendrianto; Nursimah Dara; Ahmad Bustomi (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the difference in financial performance between the profit and loss approach and the Shari'ate Value Added Statement (SVAS) at the Indonesian Benteng Mikro Syariah Cooperative. The data used is the annual financial report issued by the Indonesian micro-fortress sharia cooperative in the 2016-2020 period. The population of this study includes sharia cooperatives in Tangerang which are registered with the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia for the 2016-2020 period. The object of this research is the Indonesian micro-fortress sharia cooperative. The type of data used is secondary data obtained from the Indonesian micro-fortress sharia cooperative and its website. The analytical method used is descriptive statistical analysis. The analytical tool used in this research is the independent sample t test. The results of the calculations and the required performance ratios are compared with the results through statistical tests. The results showed that there was a significant difference in the financial performance of the Indonesian micro-fortress sharia cooperative using the ROA, ROE, and LBAP ratio measuring scale when analyzed using the profit and loss approach and the shari'ate value added statement.